The integration of international financial markets: An attempt to quantify contagion in an input-output-type analysis - Dieter Schumacher (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The increasing integration of international financial markets means that credit defaults in one country have to be covered by creditors in other countries. If the principle of creditor liability were applied systematically, the financial losses incurred by the financial institution that provided the credit and is thus directly affected by the default would be 'passed on' through its domestic and foreign shareholders and debt holders, as well as their creditors, to the original savers. In this paper, this contagion effect will be estimated by taking international capital linkages into account. Analogously to an input-output analysis of interindustry linkages, savings used for investments in one country are traced back to the countries from which the funds originated. This also reveals the important role of international financial centers, which essentially serve as distributors of investment risks, while the financial losses are ultimately borne by larger countries with higher levels of savings.
Keywords: F65; G01; G15; 330; financial crises; international capital linkages; input-output analysis